Penerapan Pendekatan Pendidikan Matematika Realistik (PMR) untuk Meningkatkan Hasil Belajar Matematika di Kelas V SDK 3 Bangunan Wuwuk - Kaesang, Anastasia I.; Rorimpandey, Widdy H. F.; Legi, Moses Y. (Jurnal Ilmiah Wahana Pendidikan, 2023)
This research aims to improve mathematics learning outcomes through the Realistic Mathematics Education (PMR) approach in class V of SDK 3 Wuwuk Building. The research method used is Classroom Action Research (PTK) which consists of planning, implementation, observation, and reflection. This research was carried out in two cycles. The subjects in this research were 11 students in class V of SDK 3 Wuwuk Building, consisting of 7 male students and 4 female students. Data collection techniques in this research are observation and tests. Data analysis to determine student learning outcomes, whether they have met the criteria for learning completeness or not. The results of the research by applying the Realistic Mathematics Education approach in mathematics learning showed that the achievement in the first cycle was 60% and the achievement in the second cycle was 86.8%. Based on the results from cycle I to cycle II, it turns out there has been an increase. Thus, it can be concluded that the application of a realistic mathematical approach can improve student learning outcomes